PENGARUH PENGGUNAAN MEDIA PEMBELAJARAN INTERAKTIF TERHADAP HASIL BELAJAR MENULIS TEKS DESKRIPTIF PADA SISWA KELAS VII SMP - Fiona Ayu Faradila; Hetilaniar; Juaidah Agustina (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Descriptive text is a composition that describes an object (in the form of people, objects, places, events and some) with words in the actual situation to the reader so that the reader seems to feel, experience, remember the events or things written by the author. Based on this, the problem in this study is how to apply learning to write descriptive texts using picture media to class VII students of SMP Negeri 4 Sungai Rotan. Objectives This research is to determine the influence of learning to write descriptive texts through interactive learning media on students in class VII of SMP Negeri 4 Sungai Rotan. The method of this research is a quantitative experiment. The results of this research show that interactive learning media has an influence on the results of learning to write descriptive texts on students in class VII of SMP Negeri 4 Sungai Rotan. Therefore, Interactive learning media can be applied in learning Indonesian.